Sodium-ion battery composite negative electrode material as well as preparation method and application thereof

By using titanium dioxide/carbon nanotube/tin composite materials as the negative electrode material in sodium ion batteries, the technical challenges of sodium ion batteries in energy density and cycle life are solved, and higher electrochemical performance and more stable battery performance are achieved.

CN119695093APending Publication Date: 2025-03-25LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311249951.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Sodium ion batteries have technical challenges in energy density, cycle life, etc., which restricts the development of their large-scale applications.

Method used

Titanium dioxide/carbon nanotube/tin composite material is used as the negative electrode material for sodium ion batteries. By compositeing carbon nanotubes with titanium oxide and electroplating tin on the surface of the material, the electrochemical performance of the material is optimized.

Benefits of technology

The energy density, cycle life and stability of the sodium ion battery are improved, and higher electrochemical performance is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695093A_ABST
    Figure CN119695093A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery composite negative electrode material and a preparation method and application thereof. The preparation method comprises the following steps: preparing a titanium dioxide aqueous solution; preparing a carbon nanotube dispersion liquid; preparing a mixed solution of a titanium dioxide aqueous solution and a carbon nanotube dispersion liquid; preparing a titanium dioxide / carbon nanotube composite nanosheet; preparing an electrotinning solution; suspending the titanium dioxide / carbon nanotube composite nanosheet in an electroplating solution, and depositing tin on the surface of the titanium dioxide / carbon nanotube composite nanosheet and / or in material gaps under certain current density and electroplating time to form a uniform coating of tin, so as to obtain a composite material precursor; and performing heat treatment on the composite material precursor to obtain the sodium-ion battery composite negative electrode material, when the composite negative electrode material disclosed by the invention is used as a negative electrode active material in the sodium-ion battery, the sodium-ion battery can have higher energy density, longer cycle life and more stable electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery materials, and in particular to a sodium ion battery composite negative electrode material and a preparation method and application thereof. Background Art

[0002] As clean energy becomes increasingly important, sodium-ion batteries have attracted widespread attention as a high-performance energy storage technology. Compared with traditional lithium-ion batteries, sodium-ion batteries have the advantages of lower cost and more abundant resources, and are considered to be a powerful choice for sustainable energy storage. However, sodium-ion batteries still face technical challenges in terms of energy density and cycle life, which restricts their development in large-scale applications.

[0003] Carbon nanotubes and titanium oxide represent the advanced fields of nanomaterials and metal oxide materials, respectively. Carbon nanotubes have gradually become a hot topic in battery material research due to their excellent conductivity, mechanical strength and chemical stability. Titanium oxide has broad application prospects in the field of energy conversion and storage due to its excellent electrochemical activity, catalytic performance and chemical stability. The composite of carbon nanotubes and titanium oxide into nanosheets brings new opportunities for the design of negative electrode materials for sodium ion batteries. This composite material may give full play to the respective advantages of carbon nanotubes and titanium oxide, such as conductivity and electrochemical activity, thereby improving the energy density and cycle life of the battery. Electroplating tin as a surface treatment method provides a powerful means for further optimization of carbon nanotube / titanium oxide composites. Electroplating tin can form a uniform thin layer of tin on the surface of the composite material, which is expected to enhance the conductivity of the material, the stability of the electrode interface, and improve the insertion / deinsertion behavior of sodium ions in the composite material, thereby improving the cycle performance and capacity retention of the battery.

[0004] Studies have reported on the application of carbon nanotube / titanium oxide materials in different fields, such as the application of electroplated tin in lithium-ion battery negative electrode materials. However, the research on the combination of these materials in sodium-ion batteries has not been fully carried out. Existing research may have problems such as short cycle life and large capacity loss, so further material design and improvement are needed. Summary of the invention

[0005] The purpose of the present invention is to provide a composite negative electrode material for a sodium ion battery, and a preparation method and application thereof, namely, a titanium dioxide / carbon nanotube / tin composite material. By compounding carbon nanotubes with titanium oxide and electroplating tin on the surface of the material, the electrochemical properties of the material are optimized to achieve higher energy density, longer cycle life and more stable battery performance. This innovative design will bring important breakthroughs in the field of sodium ion batteries.

[0006] The embodiment of the present invention provides a sodium ion battery composite negative electrode material and a preparation method and application thereof.

[0007] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a composite negative electrode material for a sodium ion battery, the preparation method comprising:

[0008] Step S1, preparing a titanium dioxide aqueous solution, specifically: slowly adding a titanium source material to deionized water, stirring in an ice water bath, adding an alkaline solution to adjust the pH value of the solution, reacting to obtain a white precipitate, collecting the white precipitate by centrifugation, washing with deionized water, re-dispersing the white precipitate in water, then dripping hydrogen peroxide until the solution is yellow and transparent, then adding deionized water to dilute, obtaining a titanium dioxide aqueous solution, and storing it in a refrigerator for later use;

[0009] Step S2, preparing a carbon nanotube dispersion, specifically: dispersing the carbon nanotubes in a nitric acid solution, performing a reflux treatment, and dispersing the carbon nanotubes in deionized water after centrifugal washing to obtain a carbon nanotube dispersion;

[0010] Step S3, preparing a mixed solution of a titanium dioxide aqueous solution and a carbon nanotube dispersion, specifically: mixing the titanium dioxide aqueous solution and the carbon nanotube dispersion, stirring and then standing for aging to obtain a mixed solution;

[0011] Step S4, preparing titanium dioxide / carbon nanotube composite nanosheets, specifically: rapidly freezing the mixed solution, and then drying to remove water, to obtain a block of titanium dioxide / carbon nanotube composite nanosheet precursor, and then sintering at high temperature to obtain the titanium dioxide / carbon nanotube composite nanosheet;

[0012] Step S5, preparing a tin electroplating solution, specifically: adding a tin salt to an appropriate amount of solvent, adding a complexing agent and a pH adjuster to adjust the pH value of the electroplating solution, stirring sufficiently to completely dissolve the tin salt, and obtaining the tin electroplating solution;

[0013] Step S6, suspending the titanium dioxide / carbon nanotube composite nanosheets in the above electroplating solution, and depositing tin on the surface of the titanium dioxide / carbon nanotube composite nanosheets and / or in the gaps between the materials at a certain current density and electroplating time to form a uniform coating of tin, thereby obtaining a composite material precursor;

[0014] Step S7, heat treating the composite material precursor to obtain a composite negative electrode material for a sodium ion battery.

[0015] Preferably, in step S1: the titanium source material includes: one or more of TiCl4, TiCl3, TiS2O8; the mass ratio of the titanium source material to deionized water is [0.2-10]:100;

[0016] The alkaline solution includes: one or more of ammonia water, potassium hydroxide, and sodium hydroxide solution; the molar concentration of the alkaline solution is 0.5 mol / L-5 mol / L;

[0017] The alkaline solution is added to adjust the pH value of the solution, and a white precipitate is obtained by reaction. The specific process is: the alkaline solution is added to adjust the pH value of the solution to between 7 and 11, and then the reaction is carried out for 6 hours to 72 hours to obtain a white precipitate;

[0018] The rotation speed of the centrifugal collection of white precipitate is 5000rpm-10000rpm;

[0019] The number of times of washing with deionized water is 3 to 5 times; the dispersing of the white precipitate in water is specifically: dispersing the white precipitate in 50 mL to 200 mL of deionized water;

[0020] The molar ratio of hydrogen peroxide to Ti in the solution is [3-20]:1;

[0021] The mass concentration of the titanium dioxide aqueous solution is 10 mg / mL.

[0022] Preferably, in step S2: the molar concentration of the nitric acid solution is 15 mol / L; the mass ratio of the nitric acid solution to the carbon nanotubes is 5000:[1-10];

[0023] The temperature of the reflux treatment is set to 120° C., and the time of the reflux treatment is 12 hours;

[0024] The mass concentration of the carbon nanotube dispersion is 10 mg / mL.

[0025] Preferably, in step S3: the mass ratio of titanium dioxide in the titanium dioxide aqueous solution to the carbon nanotubes in the carbon nanotube dispersion is [1-10]:1;

[0026] The stirring time is 6 hours; the standing aging time is 1 hour to 24 hours.

[0027] Preferably, in step S4: the mixed solution is rapidly frozen by liquid nitrogen freezing or low-temperature refrigerator freezing; the drying to remove moisture is performed by freeze drying;

[0028] The high temperature sintering is specifically as follows: placing the precursor of the titanium dioxide / carbon nanotube composite nanosheet in a tube furnace under an inert atmosphere and calcining it at a temperature of 180° C.-800° C. for a time of 30 min-240 min.

[0029] Preferably, in step S5: the tin salt comprises: one or more of tin nitrate, tin hydroxide or tin chloride; the solvent is deionized water; the complexing agent comprises: one or more of citric acid, sodium tartrate, ethylenediaminetetraacetic acid; the pH regulator comprises: sodium hydroxide and / or potassium hydroxide;

[0030] The pH value of the adjusted electroplating solution is neutral or slightly alkaline, specifically between 7 and 10; in the electroplating tin solution: the tin salt content is 10g / L-50g / L, and the complexing agent content is 5g / L-40g / L.

[0031] Preferably, in step S6: the current density is 0.5A / dm 2 -5A / dm 2 The electroplating time is 20min-60min, and the temperature during electroplating is 20℃-50℃;

[0032] In the step S7, the heat treatment is specifically as follows: placing the composite material precursor in a vacuum drying oven, heating it to 60°C-100°C at 2°C / min-5°C / min, keeping it warm for 4 hours-24 hours, and then naturally cooling it to room temperature.

[0033] In a second aspect, an embodiment of the present invention provides a sodium ion battery composite negative electrode material prepared by the preparation method described in the first aspect, wherein the sodium ion battery composite negative electrode material comprises titanium dioxide / carbon nanotube composite nanosheets, tin particles deposited on the surface of the titanium dioxide / carbon nanotube composite nanosheets and in the gap between titanium dioxide and carbon nanotubes, and tin ions Sn partially doped in titanium dioxide. 4+ .

[0034] In a third aspect, an embodiment of the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the sodium ion battery composite negative electrode material described in the second aspect above.

[0035] In a fourth aspect, an embodiment of the present invention provides a sodium ion battery, wherein the sodium ion battery comprises the negative electrode plate described in the third aspect above.

[0036] The embodiment of the present invention provides a method for preparing a composite negative electrode material for a sodium ion battery, wherein carbon nanotubes and titanium dioxide are first composited to form a titanium dioxide / carbon nanotube composite nanosheet, and then the composite nanosheet is placed in a tin electroplating solution, and tin ions are reduced and deposited on the surface of the composite nanosheet and in the gaps between titanium dioxide particles and carbon nanotubes under the action of electric current, thereby obtaining a composite negative electrode material for a sodium ion battery; the method for preparing the composite negative electrode material for a sodium ion battery is simple to operate and has low cost, and is conducive to realizing the commercial application of sodium ion batteries.

[0037] The sodium ion battery composite negative electrode material provided by the embodiment of the present invention includes titanium dioxide / carbon nanotube composite nanosheets, tin particles deposited on the surface of the composite nanosheets and in the gaps between titanium dioxide / carbon nanotubes, and tin ions Sn partially doped in titanium dioxide. 4+; The structure of the composite nanosheet is based on titanium oxide particles as a substrate, and then carbon nanotubes are dispersed on the surface or in the gaps of titanium oxide particles at nanoscale on the surface of the material, and are intertwined with titanium oxide by adsorption, physical entanglement, etc. This structure can give full play to the conductivity of carbon nanotubes and the electrochemical activity of titanium dioxide, and the deposited tin and the tin ions in the partially doped titanium dioxide can improve the stability and catalytic activity of titanium dioxide; the electrochemical properties of the material are optimized through the synergistic effect of the above-mentioned titanium dioxide / carbon nanotube composite nanosheet, the deposited tin, and the doped tin ions; the sodium ion battery composite negative electrode material of the present invention is applied to sodium ion batteries, so that the sodium ion batteries have higher energy density, longer cycle life and more stable electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.

[0039] Figure 1 It is a flow chart of a method for preparing a composite negative electrode material for a sodium ion battery provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0041] The present invention provides a method for preparing a composite negative electrode material for a sodium ion battery. Figure 1 As shown, the specific steps include:

[0042] Step S1, preparing a titanium dioxide aqueous solution;

[0043] The specific preparation process is as follows: slowly add the titanium source material into deionized water, stir in an ice water bath, add an alkaline solution to adjust the pH value of the solution, react to obtain a white precipitate, collect the white precipitate by centrifugation, wash with deionized water, disperse the white precipitate in water again, then drop hydrogen peroxide until the solution is yellow and transparent, then add deionized water to dilute, obtain a titanium dioxide aqueous solution, and store it in a refrigerator for later use;

[0044] The titanium source material includes one or more of TiCl4, TiCl3, and TiS2O8; the mass ratio of the titanium source material to deionized water is [0.2-10]:100; the alkaline solution includes one or more of ammonia water, potassium hydroxide, and sodium hydroxide solution; the molar concentration of the alkaline solution is 0.5 mol / L-5 mol / L;

[0045] An alkaline solution is added to adjust the pH value of the solution, and a white precipitate is obtained by reaction. The specific process is: an alkaline solution is added to adjust the pH value of the solution to between 7 and 11, and then the reaction is carried out for 6 hours to 72 hours to obtain a white precipitate; the rotation speed when the white precipitate is collected by centrifugation is 5000 rpm to 10000 rpm;

[0046] The number of times of washing with deionized water is 3 to 5 times; the white precipitate is dispersed in water, specifically: the white precipitate is dispersed in 50 mL to 200 mL of deionized water;

[0047] The molar ratio of hydrogen peroxide to Ti in the solution is [3-20]:1; the mass concentration of the titanium dioxide aqueous solution is 10 mg / mL.

[0048] Step S2, preparing a carbon nanotube dispersion;

[0049] The specific process is as follows: dispersing carbon nanotubes in a nitric acid solution, performing a reflux treatment, and dispersing the carbon nanotubes in deionized water after centrifugal washing to obtain a carbon nanotube dispersion;

[0050] The molar concentration of the nitric acid solution is 15 mol / L; the mass ratio of the nitric acid solution to the carbon nanotubes is 5000:[1-10];

[0051] The temperature of the reflux treatment was set to 120°C, and the reflux treatment time was 12 hours;

[0052] The mass concentration of the carbon nanotube dispersion is 10 mg / mL, and the carbon nanotubes (CNTs) of the present invention are multi-walled carbon nanotubes;

[0053] In this step, nitric acid solution is used to disperse the carbon nanotubes, which helps to disperse the agglomerated carbon nanotubes so that they can be evenly suspended in the liquid;

[0054] The surface oxidation reaction is induced by reflux treatment in a nitric acid solution, so that the surface of the carbon nanotubes is oxidized, thereby producing oxidized carbon nanotubes containing functional groups such as hydroxyl and carboxyl groups. These functional groups can increase the interaction between the carbon nanotubes and other molecules, thereby improving their dispersibility and compatibility with other substances; and the reflux treatment can also help to clean and remove impurities and impure substances on the surface of the carbon nanotubes, thereby improving the purity of the carbon nanotubes.

[0055] Step S3, preparing a mixed solution of a titanium dioxide aqueous solution and a carbon nanotube dispersion;

[0056] Specifically, the titanium dioxide aqueous solution and the carbon nanotube dispersion are mixed, stirred, and then allowed to stand for aging to obtain a mixed solution;

[0057] The mass ratio of titanium dioxide in the titanium dioxide aqueous solution to carbon nanotubes in the carbon nanotube dispersion is [1-10]:1; the stirring time is 6 hours; the static aging time is 1 hour to 24 hours;

[0058] During the static aging process in this step, some functional groups on the surfaces of titanium dioxide and carbon nanotubes, such as hydroxyl and carboxyl, will cause physical adsorption and interaction between titanium dioxide particles and carbon nanotubes during the aging process, thereby making them more closely combined.

[0059] Step S4, preparing titanium dioxide / carbon nanotube composite nanosheets;

[0060] Specifically, the mixed solution is quickly frozen, and then dried to remove water to obtain a precursor of a block of titanium dioxide / carbon nanotube composite nanosheets, and then sintered at high temperature to obtain titanium dioxide / carbon nanotube composite nanosheets;

[0061] The mixed solution can be quickly frozen by liquid nitrogen freezing or low-temperature refrigerator freezing; and the water can be dried by freeze drying;

[0062] The high temperature sintering is specifically as follows: the precursor of the titanium dioxide / carbon nanotube composite nanosheet is placed in a tube furnace and calcined under an inert atmosphere, the calcination temperature is 180° C.-800° C., and the calcination time is 30 min-240 min.

[0063] Step S5, preparing a tin electroplating solution;

[0064] Specifically, the tin salt is added to an appropriate amount of solvent, and a complexing agent and a pH regulator are added at the same time to adjust the pH value of the electroplating solution, and the solution is stirred sufficiently to completely dissolve the tin salt to obtain an electroplating tin solution;

[0065] Wherein, the tin salt includes: one or more of tin nitrate, tin hydroxide or tin chloride; the solvent is deionized water; the complexing agent includes: one or more of citric acid, sodium tartrate, ethylenediaminetetraacetic acid; the pH adjusting agent includes: sodium hydroxide and / or potassium hydroxide; the pH value of the electroplating solution is adjusted to be neutral or slightly alkaline, specifically between 7-10;

[0066] In the electroplating tin solution: the tin salt content is 10g / L-50g / L; the amount of complexing agent added is between 5g / L-40g / L, and can be any value within this range, including but not limited to 5g / L, 10g / L, 15g / L, 20g / L, 25g / L, 30g / L, 35g / L, 40g / L; the complexing agent forms a tin complex with tin ions, which can effectively improve the stability of tin ions and promote the deposition of tin ions, thereby improving the performance of pure tin electroplating. .

[0067] Step S6, suspending the titanium dioxide / carbon nanotube composite nanosheets in the above electroplating solution, and depositing tin on the surface of the titanium dioxide / carbon nanotube composite nanosheets and / or in the gaps between the materials at a certain current density and electroplating time to form a uniform coating of tin, thereby obtaining a composite material precursor;

[0068] Among them, the current density is 0.5A / dm 2 -5A / dm 2 ; The electroplating time is 20min-60min, and the temperature during electroplating is 20℃-50℃;

[0069] During the tin electroplating process, tin ions will be reduced and deposited as metallic tin on the surface of the composite nanosheets. The deposition of tin will first occur preferentially on the outer surface of the composite nanosheets. As the electroplating continues, tin will gradually form a uniform tin coating on the surface of the nanosheets.

[0070] When the tin ions in the plating solution are reduced and deposited on the nanosheets, tin will preferentially deposit on the surface of the nanosheets because the surface is the main site of electrochemical reactions; however, there may also be a certain degree of electrochemical reaction in areas such as the gaps, pores and depressions of the nanosheets; this means that the tin ions will enter the gaps between titanium dioxide and carbon nanotubes and partially deposit in these areas; this situation will cause some tin particles to coexist on the surface of the nanosheets and in the gaps between titanium dioxide and carbon nanotubes.

[0071] Step S7, heat treating the composite material precursor to obtain a composite negative electrode material for a sodium ion battery;

[0072] The heat treatment is specifically as follows: placing the composite material precursor in a vacuum drying oven, heating it to 60°C-100°C at 2°C / min-5°C / min, keeping it warm for 4 hours-24 hours, and then naturally cooling it to room temperature.

[0073] The present invention provides a composite negative electrode material for a sodium ion battery prepared by the above-mentioned preparation method, comprising a titanium dioxide / carbon nanotube composite nanosheet, tin particles deposited on the surface of the composite nanosheet and in the gaps between the titanium dioxide / carbon nanotubes, and tin ions Sn partially doped in the titanium dioxide. 4+; Among them, the structure of the titanium dioxide / carbon nanotube composite nanosheet is based on titanium oxide particles as the substrate, and then the carbon nanotubes are dispersed on the surface or in the gaps of the titanium oxide particles at the nanoscale on the surface of the material, and are intertwined with the titanium oxide by adsorption, physical entanglement, etc. This structure can give full play to the conductivity of the carbon nanotubes and the electrochemical activity of titanium dioxide, the deposited tin particles and the tin ions in the partially doped titanium dioxide, among which the tin particles can play a catalytic role, and the doped tin ions can avoid or reduce the hydrolysis of titanium dioxide, thereby improving the stability and catalytic activity of titanium dioxide; the electrochemical properties of the material are optimized through the synergistic effect of the above-mentioned titanium dioxide / carbon nanotube composite nanosheets, deposited tin, and doped tin ions.

[0074] The sodium ion battery composite negative electrode material provided in the embodiment of the present invention can be used as a negative electrode active material in a sodium ion battery, so that the sodium ion battery has a higher energy density, a longer cycle life and a more stable electrochemical performance.

[0075] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the composite negative electrode material for sodium ion batteries of the present invention are respectively described below with multiple specific examples.

[0076] Example 1

[0077] This embodiment provides a preparation process and performance test of a composite negative electrode material for a sodium ion battery. The specific preparation process is as follows:

[0078] (1) preparing a titanium dioxide aqueous solution, specifically: in a fume hood, slowly adding 0.78 ml (8 mmol) of TiCl4 to 125 ml of deionized water at 4°C, stirring in an ice-water bath for 1 hour, then slowly dropping ammonia water (molar concentration of 0.5 mol / L), and adjusting the pH of the mixed solution to 7; after reacting for 6 hours, a white precipitate of Ti(OH)4 is obtained; the white precipitate is redispersed in 50 ml of deionized water, and centrifuged at 6000 rpm, and this washing step is repeated 3 times; the white precipitate is again dispersed in 50 ml of deionized water, and 8 ml of hydrogen peroxide is added until the solution becomes yellow and transparent, forming a titanium dioxide aqueous solution; the titanium dioxide aqueous solution is diluted to a mass concentration of 10 mg / mL, and stored at 4°C.

[0079] (2) preparing a carbon nanotube dispersion, the specific process is as follows: adding 0.1 g of carbon nanotubes with a diameter of 15 nm into a 15 mol / L concentrated nitric acid solution and refluxing at 120° C. for 12 hours, then centrifuging and washing at a speed of 6000 rpm for 5 times, and then dispersing the carbon nanotubes in deionized water to ensure that the mass concentration is 10 mg / ml to obtain a carbon nanotube dispersion.

[0080] (3) 10 ml of the titanium dioxide aqueous solution and 2 ml of the carbon nanotube dispersion were mixed, diluted to 2.5 mg / ml with deionized water, stirred for 6 hours, and then allowed to stand for 6 hours to age, to obtain a mixed solution.

[0081] (4) preparing titanium dioxide / carbon nanotube composite nanosheets, specifically: the mixture prepared in the previous step is quickly frozen with liquid nitrogen, and then dried with a freeze dryer to obtain a block of titanium dioxide / carbon nanotube composite nanosheet precursor, which is placed in a tubular furnace, and heated to 500°C at a rate of 5°C / min in a nitrogen atmosphere, kept at this temperature for 1 hour, and then naturally cooled to obtain the titanium dioxide / carbon nanotube composite nanosheet.

[0082] (5) preparing an electroplating tin solution, specifically, adding 10 g of tin chloride into 1000 ml of deionized water, adding 5 g of a complexing agent, sodium tartrate, and adding sodium hydroxide to adjust the pH value of the electroplating solution to 7, stirring sufficiently to completely dissolve the tin salt, and fully dispersing the solution in an ultrasonic disperser to obtain an electroplating tin solution.

[0083] (6) suspending the titanium dioxide / carbon nanotube composite nanosheets in the above-mentioned fully dispersed electroplating solution at 1A / dm 2 Electroplating was performed for 20 minutes at a current density of 1.5 Å, and the temperature of the electroplating solution was maintained at 50° C., so that tin was deposited on the surface and in the gaps of the titanium dioxide / carbon nanotube composite nanosheets of the nanosheets to form a uniform coating with a thickness of 3 μm, thereby obtaining a composite material precursor.

[0084] (7) The composite material precursor is placed in a vacuum drying oven, heated to 60°C at a rate of 5°C / min, kept warm for 12 hours, and then naturally cooled to room temperature to obtain a composite negative electrode material for a sodium ion battery.

[0085] The sodium ion battery composite negative electrode material prepared in this embodiment is used to prepare the negative electrode sheet and assemble the battery for testing. The specific process is as follows:

[0086] Preparation of negative electrode sheet: The prepared sodium ion battery composite negative electrode material is used as the negative electrode active material, and the mass ratio of negative electrode active material: conductive carbon black (SP): polyvinylidene fluoride (PVDF) = 90:5:5 is used. The slurry is prepared by taking the total material amount of 15g as an example. The specific process is as follows: 0.75g of PVDF is added to 24.25g of N-methylpyrrolidone (NMP) in a disperser, and the colloid solution is dispersed at 2000r / min until it is clear; 0.7 5g of SP was added to the glue solution and dispersed at 2000r / min for 40min; 13.5g of negative electrode active material was added to the slurry and dispersed at 2000r / min for 40min, and an appropriate amount of NMP was added to adjust the viscosity to 2000mPa.s to obtain negative electrode slurry; the negative electrode slurry was sieved with a 180-mesh screen and then coated; the coated electrode was dried at 110°C; after drying, it was cut into a circular electrode with a diameter of 8mm. Under vacuum conditions, the electrode was dried at 120°C for 6 hours and then transferred to a glove box for standby use.

[0087] Assembling button cells: The assembly of simulated batteries was carried out in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1 mol of NaPF6 dissolved in 1 L of a solution of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1 as the electrolyte to prepare a button cell.

[0088] The test procedure for button cells is: let stand for 8 hours in advance; then discharge at a rate (0.1C, 0V), discharge at a rate (0.02C, 0V), and let stand for 5 minutes; charge at a rate (0.1C, 2V), and let stand for 5 minutes; test the charge specific capacity and the first-cycle coulomb efficiency, and then test the cycle capacity retention rate after 100, 200, 300, and 500 cycles. The test results are shown in Table 1.

[0089] Example 2

[0090] This embodiment provides a preparation process of a composite negative electrode material for a sodium ion battery. The difference from Embodiment 1 is that another tin source is used to configure a different electroplating tin solution. The other preparation processes are the same as those in Embodiment 1, as follows.

[0091] The preparation process of steps (1) to (4) is the same as that of Example 1.

[0092] (5) preparing an electro-tin solution, specifically, dissolving 12 g of tin nitrate and 8 g of citric acid in 1200 ml of deionized water, adding sodium hydroxide to adjust the pH value of the electroplating solution to 7, stirring sufficiently to completely dissolve the tin salt, and fully dispersing the mixture in an ultrasonic disperser to obtain an electro-tin solution.

[0093] (6) suspending the titanium dioxide / carbon nanotube composite nanosheets in the above-mentioned fully dispersed electroplating solution at 2A / dm 2Electroplating was performed for 30 minutes at a current density of 50° C., and the temperature of the electroplating solution was maintained at 50° C., so that tin was deposited on the surface and in the gaps of the titanium dioxide / carbon nanotube composite nanosheets of the nanosheets to form a uniform coating of 3 μm thick tin, thereby obtaining a composite material precursor.

[0094] (7) The composite material precursor is placed in a vacuum drying oven, heated to 90°C at a rate of 5°C / min, kept at this temperature for 1 hour, and then naturally cooled to room temperature to obtain a composite negative electrode material for a sodium ion battery.

[0095] The sodium ion battery composite negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are shown in Table 1.

[0096] Example 3

[0097] This embodiment provides a preparation process of a composite negative electrode material for a sodium ion battery. The difference from Embodiment 1 is that another titanium source is used to prepare a different titanium dioxide aqueous solution. The other preparation processes are the same as those in Embodiment 1, as follows.

[0098] (1) preparing a titanium dioxide aqueous solution, specifically: in a fume hood, slowly adding 15 mmol (2.77 g) of TiCl3 to 150 ml of deionized water at 4°C, stirring in an ice-water bath for 1 hour, then slowly dropping ammonia water to adjust the pH of the mixed solution to 7; after reacting for 5 hours, a white precipitate of Ti(OH)4 is obtained; the white precipitate is redispersed in 50 ml of deionized water, and centrifuged at 6000 rpm, and this washing step is repeated 3 times; the white precipitate is again redispersed in 50 ml of deionized water, and 5 ml of hydrogen peroxide is added until the solution becomes yellow and transparent, thereby forming a titanium dioxide aqueous solution; the titanium dioxide aqueous solution is diluted to a mass concentration of 10 mg / mL, and stored at 4°C.

[0099] The preparation process of steps (2) to (7) is the same as that of Example 1.

[0100] The sodium ion battery composite negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are shown in Table 1.

[0101] Example 4

[0102] This embodiment provides a preparation process of a composite negative electrode material for a sodium ion battery. The difference from Embodiment 1 is that step (6) changes the electroplating parameters to use 1.5 A / dm 2 The current density was 0.17 W and the electroplating was carried out at 40° C. for 30 min to obtain a tin coating with a thickness of 10 μm. The other preparation processes were the same as those in Example 1.

[0103] The sodium ion battery composite negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are shown in Table 1.

[0104] Example 5

[0105] This embodiment provides a preparation process of a composite negative electrode material for a sodium ion battery. The difference from Embodiment 1 is that step (6) changes the electroplating parameters to use 0.5 A / dm 2 The current density was 0.17 W and the electroplating was carried out at 40° C. for 10 min to obtain a tin coating with a thickness of 2 μm-3 μm. The other preparation processes were the same as those in Example 1.

[0106] The sodium ion battery composite negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are shown in Table 1.

[0107] Example 6

[0108] This embodiment provides a preparation process of a composite negative electrode material for a sodium ion battery, which is different from that in embodiment 1 in that the pH regulator ammonia water in step (1) is replaced with sodium hydroxide (molar concentration of 2 mol / L), which can adjust the pH value of the solution more quickly. The other steps are the same as those in embodiment 1.

[0109] The sodium ion battery composite negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are shown in Table 1.

[0110] Example 7

[0111] This embodiment provides a preparation process of a composite negative electrode material for a sodium ion battery, which is different from that in Example 1 in that the heat treatment conditions in step (7) are changed to heating to 100°C at 5°C / min, keeping the temperature for 6 hours, and then naturally cooling to room temperature to obtain a composite negative electrode material for a sodium ion battery. The other preparation steps are the same as those in Example 1.

[0112] The sodium ion battery composite negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are shown in Table 1.

[0113] Example 8

[0114] This embodiment provides a preparation process of a composite negative electrode material for a sodium ion battery, which is different from that of Embodiment 1 in that the content of each material in the electroplating tin solution in step (5) is as follows: 20 g of tin chloride is added to 1000 ml of deionized water, 10 g of a complexing agent, sodium tartrate, and potassium hydroxide is added to adjust the pH value of the electroplating solution to 7, and the solution is stirred sufficiently to completely dissolve the tin salt, and the solution is fully dispersed in an ultrasonic disperser to obtain an electroplating tin solution. The other preparation steps are the same as those of Embodiment 1.

[0115] The sodium ion battery composite negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are shown in Table 1.

[0116] Example 9

[0117] The present embodiment provides a preparation process of a composite negative electrode material for a sodium ion battery, which is different from the embodiment 1 in that, in step (1), an ammonia solution is added to adjust the pH value of the solution to 10, and then the reaction is carried out for 10 hours to obtain a white precipitate Ti(OH)4; the white precipitate is redispersed in 100 ml of deionized water and centrifuged at 8000 rpm, and the washing step is repeated 3 times; the white precipitate is again dispersed in 50 ml of deionized water, and 15 ml of hydrogen peroxide is added dropwise until the solution becomes yellow and transparent to form a titanium dioxide aqueous solution; the titanium dioxide aqueous solution is diluted to a mass concentration of 10 mg / ml and stored at 4°C.

[0118] The sodium ion battery composite negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are shown in Table 1.

[0119] Example 10

[0120] This embodiment provides a preparation process of a composite negative electrode material for a sodium ion battery, which is different from that of embodiment 1 in that the aging time is extended in step (3), specifically: 10 ml of a titanium dioxide aqueous solution is mixed with 2 ml of a carbon nanotube dispersion, and diluted to 2.5 mg / ml with deionized water, stirred for 10 hours, and then aged for 12 hours to obtain a mixed solution. The other preparation steps are the same as those of embodiment 1.

[0121] The sodium ion battery composite negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are shown in Table 1.

[0122] In order to better illustrate the effects of the embodiments of the present invention, comparative examples 1-2 are compared with the above embodiments.

[0123] Comparative Example 1

[0124] In this comparative example, conventional titanium dioxide was electroplated to form a tin deposition layer as the negative electrode material, negative electrode plates were prepared and batteries were assembled for testing. The battery assembly and testing process were the same as those in Example 1. The test results are shown in Table 1.

[0125] (1) preparing an electroplating tin solution, specifically, adding 10 g of tin chloride into 1000 ml of deionized water, adding 5 g of a complexing agent, sodium tartrate, adding sodium hydroxide to adjust the pH value of the electroplating solution to 7, stirring sufficiently to completely dissolve the tin salt, and sufficiently dispersing the solution in an ultrasonic disperser to obtain an electroplating tin solution.

[0126] (2) suspending nano-titanium dioxide particles in the above-mentioned fully dispersed electroplating solution at 1A / dm 2 The electroplating was performed for 20 minutes at a current density, and the temperature of the electroplating solution was maintained at 50° C., so that tin was deposited on the surface of the nano-titanium dioxide particles to form a uniform tin coating with a thickness of 3 μm, thereby obtaining a composite material precursor.

[0127] (3) The composite material precursor was placed in a vacuum drying oven, heated to 60° C. at a rate of 5° C. / min, kept warm for 12 hours, and then naturally cooled to room temperature to obtain a tin-plated nano-titanium dioxide particle composite negative electrode material for comparison.

[0128] The sodium ion battery composite negative electrode material prepared in this comparative example was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are shown in Table 1.

[0129] Comparative Example 2

[0130] In this comparative example, nano-tin particles and titanium dioxide / carbon nanotube matrix were composited to prepare negative electrode materials, negative electrode plates were prepared and batteries were assembled for testing. The battery assembly and testing process were the same as those in Example 1. The test results are shown in Table 1.

[0131] (1) preparing a titanium dioxide aqueous solution, specifically: in a fume hood, slowly adding 0.78 ml (8 mmol) of TiCl4 to 125 ml of deionized water at 4°C, stirring in an ice-water bath for 1 hour, then slowly dropping ammonia water (molar concentration of 0.5 mol / L), and adjusting the pH of the mixed solution to 7; after reacting for 6 hours, a white precipitate of Ti(OH)4 is obtained; the white precipitate is redispersed in 50 ml of deionized water, and centrifuged at 6000 rpm, and this washing step is repeated 3 times; the white precipitate is again dispersed in 50 ml of deionized water, and 8 ml of hydrogen peroxide is added until the solution becomes yellow and transparent, forming a titanium dioxide aqueous solution; the titanium dioxide aqueous solution is diluted to a mass concentration of 10 mg / ml, and stored at 4°C.

[0132] (2) preparing a carbon nanotube dispersion, the specific process is as follows: adding 0.1 g of carbon nanotubes with a diameter of 15 nm into a 15 mol / L concentrated nitric acid solution and refluxing at 120° C. for 12 hours, then centrifuging and washing at a speed of 6000 rpm for 5 times, and then dispersing the carbon nanotubes in deionized water to ensure that the mass concentration is 10 mg / ml to obtain a carbon nanotube dispersion.

[0133] (3) 10 ml of the above titanium dioxide aqueous solution was mixed and dispersed with 2 ml of carbon nanotube dispersion and 1 g of 5 nm nanotin particles, and diluted to 2.5 mg / ml with deionized water. After stirring for 6 hours, the mixture was aged for 6 hours to obtain a mixed solution. The mixed solution was quickly frozen with liquid nitrogen and then dried with a freeze dryer to obtain titanium dioxide / carbon nanotube composite nanosheets containing nanotin.

[0134] The sodium ion battery composite negative electrode material prepared in this comparative example was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are shown in Table 1.

[0135] Table 1 is a summary of the test data of button batteries assembled in Examples 1-10 and Comparative Examples 1-2:

[0136]

[0137] Table 1

[0138] By comparing the test data in Table 1, it can be seen that the first-week coulombic efficiency, charge specific capacity and capacity retention rate of 200, 300 and 500 cycles of Examples 1-10 are better than those of Comparative Examples 1-2. This is because the structure of the titanium dioxide / carbon nanotube composite nanosheets contained in the sodium ion battery composite negative electrode material prepared in the embodiment of the present invention is based on titanium oxide particles as a substrate, and then the carbon nanotubes are dispersed on the surface or gaps of the titanium oxide particles at a nanoscale on the surface of the material, and intertwined with the titanium oxide by adsorption, physical entanglement, etc. This structure can not only improve the conductivity of the matrix through the carbon nanotubes, but also improve the conductivity of the matrix through the carbon nanotubes. The composite structure suppresses the volume effect of tin in the process of embedding and de-embedding sodium ions. It can be seen from Comparative Example 1 that the structure can improve the cyclic stability of the material. The deposited tin particles and the tin ions in the partially doped titanium dioxide can improve the stability and catalytic activity of titanium dioxide. It can be found from Comparative Example 2 that the tin-containing composite material prepared by electroplating tin has a higher first efficiency and specific capacity than the composite material prepared by nano-tin particles, and also has cyclic stability. The electrochemical properties of the material are optimized through the synergistic effect of the above-mentioned titanium dioxide / carbon nanotube composite nanosheets, deposited tin, and doped tin ions.

[0139] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a composite negative electrode material for a sodium ion battery, characterized in that: The preparation method comprises: Step S1, preparing a titanium dioxide aqueous solution, specifically: slowly adding a titanium source material to deionized water, stirring in an ice water bath, adding an alkaline solution to adjust the pH value of the solution, reacting to obtain a white precipitate, collecting the white precipitate by centrifugation, washing with deionized water, re-dispersing the white precipitate in water, then dripping hydrogen peroxide until the solution is yellow and transparent, then adding deionized water to dilute, obtaining a titanium dioxide aqueous solution, and storing it in a refrigerator for later use; Step S2, preparing a carbon nanotube dispersion, specifically: dispersing the carbon nanotubes in a nitric acid solution, performing a reflux treatment, and dispersing the carbon nanotubes in deionized water after centrifugal washing to obtain a carbon nanotube dispersion; Step S3, preparing a mixed solution of a titanium dioxide aqueous solution and a carbon nanotube dispersion, specifically: mixing the titanium dioxide aqueous solution and the carbon nanotube dispersion, stirring and then standing for aging to obtain a mixed solution; Step S4, preparing titanium dioxide / carbon nanotube composite nanosheets, specifically: rapidly freezing the mixed solution, and then drying to remove water, to obtain a block of titanium dioxide / carbon nanotube composite nanosheet precursor, and then sintering at high temperature to obtain the titanium dioxide / carbon nanotube composite nanosheet; Step S5, preparing a tin electroplating solution, specifically: adding a tin salt to an appropriate amount of solvent, adding a complexing agent and a pH adjuster to adjust the pH value of the electroplating solution, stirring sufficiently to completely dissolve the tin salt, and obtaining the tin electroplating solution; Step S6, suspending the titanium dioxide / carbon nanotube composite nanosheets in the above electroplating solution, and depositing tin on the surface of the titanium dioxide / carbon nanotube composite nanosheets and / or in the gaps between the materials at a certain current density and electroplating time to form a uniform coating of tin, thereby obtaining a composite material precursor; Step S7, heat treating the composite material precursor to obtain a composite negative electrode material for a sodium ion battery.

2. The preparation method according to claim 1, characterized in that: In the step S1: the titanium source material includes: one or more of TiCl4, TiCl3, TiS2O8; the mass ratio of the titanium source material to deionized water is [0.2-10]:100; The alkaline solution includes: one or more of ammonia water, potassium hydroxide, and sodium hydroxide solution; the molar concentration of the alkaline solution is 0.5 mol / L-5 mol / L; The alkaline solution is added to adjust the pH value of the solution, and a white precipitate is obtained by reaction. The specific process is: the alkaline solution is added to adjust the pH value of the solution to between 7 and 11, and then the reaction is carried out for 6 hours to 72 hours to obtain a white precipitate; The rotation speed of the centrifugal collection of white precipitate is 5000rpm-10000rpm; The number of times of washing with deionized water is 3 to 5 times; the dispersing of the white precipitate in water is specifically: dispersing the white precipitate in 50 mL to 200 mL of deionized water; The molar ratio of hydrogen peroxide to Ti in the solution is [3-20]:1; The mass concentration of the titanium dioxide aqueous solution is 10 mg / mL.

3. The preparation method according to claim 1, characterized in that: In the step S2: the molar concentration of the nitric acid solution is 15 mol / L; the mass ratio of the nitric acid solution to the carbon nanotubes is 5000:[1-10]; The temperature of the reflux treatment is set to 120° C., and the time of the reflux treatment is 12 hours; The mass concentration of the carbon nanotube dispersion is 10 mg / mL.

4. The preparation method according to claim 1, characterized in that: In the step S3: the mass ratio of titanium dioxide in the titanium dioxide aqueous solution to the carbon nanotubes in the carbon nanotube dispersion is [1-10]:1; The stirring time is 6 hours; the standing aging time is 1 hour to 24 hours.

5. The preparation method according to claim 1, characterized in that: In step S4, the mixed solution can be rapidly frozen by liquid nitrogen freezing or low-temperature refrigerator freezing; the drying to remove moisture can be performed by freeze drying; The high temperature sintering is specifically as follows: placing the precursor of the titanium dioxide / carbon nanotube composite nanosheet in a tube furnace under an inert atmosphere and calcining it at a temperature of 180° C.-800° C. for a time of 30 min-240 min.

6. The preparation method according to claim 1, characterized in that: In step S5, the tin salt includes one or more of tin nitrate, tin hydroxide or tin chloride; the solvent is deionized water; the complexing agent includes one or more of citric acid, sodium tartrate and ethylenediaminetetraacetic acid; the pH regulator includes sodium hydroxide and / or potassium hydroxide; The pH value of the electroplating solution is adjusted to be neutral or slightly alkaline, specifically between 7 and 10; In the electrotin plating solution, the content of tin salt is 10g / L-50g / L, and the content of complexing agent is 5g / L-40g / L.

7. The preparation method according to claim 1, characterized in that: In step S6: the current density is 0.5A / dm 2 -5A / dm 2 The electroplating time is 20min-60min, and the temperature during electroplating is 20℃-50℃; In the step S7, the heat treatment is specifically as follows: placing the composite material precursor in a vacuum drying oven, heating it to 60°C-100°C at 2°C / min-5°C / min, keeping it warm for 4 hours-24 hours, and then naturally cooling it to room temperature.

8. A composite negative electrode material for a sodium ion battery prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The composite negative electrode material of the sodium ion battery comprises a titanium dioxide / carbon nanotube composite nanosheet, tin particles deposited on the surface of the titanium dioxide / carbon nanotube composite nanosheet and in the gap between titanium dioxide and carbon nanotubes, and tin ions Sn partially doped in the titanium dioxide. 4+ .

9. A negative electrode plate, characterized in that: The negative electrode plate comprises the sodium ion battery composite negative electrode material as described in claim 8 above.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the negative electrode sheet as described in claim 9 above.